Inguinoscrotal (herniated) hidatid echinococcosis - Lockhart, Jorge; Cassinelli, Juan F (Cirugía del Uruguay, 2020)
Inguinoscrotal hidatid echinococcosis of a hernia is studied. The main characteristics of a special case are the following: 1) It was secondary to a visceral intra peritoneal hydatid disease which produced a rupture. 2) There was a previous hernial process. 3) Consequently, an intrascrotal process with torpid evolution and with paquivaginalitis characteristics was produced.